2013
DOI: 10.1093/aler/aht017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Immigration on Crime

Abstract: Since the 1960s both crime rates and the share of immigrants among the American population have more than doubled. Almost three quarters of Americans believe immigration increases crime, yet existing academic research has shown no such effect. Using panel data on US counties from 1980 to 2000, this paper presents empirical evidence on a systematic and economically meaningful impact of immigration on crime. Consistent with the economic model of crime this effect is strongest for crimes motivated by financial ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 24 publications
4
28
0
2
Order By: Relevance
“…In studies that found that crime increased, this increase was mediated not by increases in immigration but by a different variable-such as reduced labor market opportunities or family structure-and differences in incarceration rates due to pre-detention practices and racial profiling (Hagan and Palloni 1999). Spenkuch (2013) finds that immigration is correlated with an increase in financial-related crime, such as theft, but only when increased immigration is coupled with poor labor market opportunities.…”
Section: Empirical Links Between Immigration and Crimementioning
confidence: 97%
“…In studies that found that crime increased, this increase was mediated not by increases in immigration but by a different variable-such as reduced labor market opportunities or family structure-and differences in incarceration rates due to pre-detention practices and racial profiling (Hagan and Palloni 1999). Spenkuch (2013) finds that immigration is correlated with an increase in financial-related crime, such as theft, but only when increased immigration is coupled with poor labor market opportunities.…”
Section: Empirical Links Between Immigration and Crimementioning
confidence: 97%
“…Thus, the instrument satisfies the condition that it is predictive of variation in undocumented immigration, however, as identified in similar strategies adopted by MacDonald, Hipp, and Gill (2013); Lyons, Vélez, and Santoro (2013); and Spenkuch (2014), the 1980 undocumented population should be theoretically independent of the change in crime rates during this period. As a result, this model breaks the simultaneity between undocumented immigration and crime and provides an exogenous test of the effect of increased undocumented immigration between 1990 and 2014 on changes in violence during this period.…”
Section: Selective Migrationmentioning
confidence: 99%
“…Although panel data techniques alleviate this problem by controlling for unobserved time-invariant location characteristics (see, Butcher and Piehl 1998;Ousey and Hubrin 2009;Wadswarth 2010), they do not solve it completely, as there might always be unobserved time-varying features that affect both location decisions and crime rates. Some researchers attempted to deal with this problem by using instrumental variables techniques, trying to find exogenous variations that affect immigrants' choice of location but not unobserved factors that affect crime rates (see, Spenkuch 2013;Bianchi et al 2012;. http://www.izajom.com/content/3/1/12…”
Section: Theoretical Views and A Brief Literature Review On Immigratimentioning
confidence: 99%